Physical and Mechanical Properties of Onion (Allium Cepa L.) Crop Relevant to Mechanical Detopping - Rani, Vijaya; Srivastava, A P (Journal of Agricultural Engineering, 2006)
The physical and mechanical properties of the onion crop were determined for the three varieties viz Agrifound Dark Red, Pusa Red and NP-53. Pusa Red variety was larger in size than the other two varieties. The linear relationship was observed between polar diameter and equatorial diameter and also weight of the bulbs (with leaf). The shape of the onion crop may be considered oblate to spherical. The mean shear force required to cut the neck for Agrifound Dark Red, Pusa Red and NP-53 was 16.23, 17.67 and 18 kgf, respectively. The cutting force increased with neck diameter for all the three varieties. The mean length and number of leaves varied from 30.85 to 36.68 mm and from 8 to 10 for the three varieties of the onion crop. The Pusa red variety was found to be denser (270 kg/mÂ³) than the other two varieties. The mean coefficient of static friction had inverse relationship with equatorial diameter and the values were 0.43, 0.41 and 0.41, respectively for the three onion varieties.